Hypohidrotic Ectodermal Dysplasia, Osteopetrosis, Lymphedema, and Immunodeficiency in an Infant with Multiple Opportunistic Infections. Issue 6 (14th February 2013) - Carlberg, Valerie M.; Lofgren, Sabra M.; Mann, Julianne A.; Austin, Jared P.; Nolt, Dawn; Shereck, Evan B.; Davila‐Saldana, Blachy; Zonana, Jonathan; Krol, Alfons L.
Abstract Osteopetrosis, lymphedema, hypohidrotic ectodermal dysplasia, and immunodeficiency (OL‐HED‐ID) is a rare X‐linked disorder with only three reported prior cases in the English‐language literature. We describe a case of OL‐HED‐ID in a male infant who initially presented with congenital lymphedema, leukocytosis, and thrombocytopenia of unknown etiology at 7 days of age. He subsequently developed gram‐negative sepsis and multiple opportunistic infections including high‐level cytomegalovirus viremia and Pneumocystis jiroveci pneumonia. The infant was noted to have mildly xerotic skin, fine sparse hair, and periorbital wrinkling, all features suggestive of ectodermal dysplasia. Skeletal imaging showed findings consistent with osteopetrosis, and immunologic investigation revealed hypogammaglobulinemia and mixed T‐ and B‐cell dysfunction. Genetic testing revealed a novel mutation in the nuclear factor kappa beta (NF‐KB) essential modulator (NEMO) gene, confirming the diagnosis of OL‐HED‐ID. Mutations in the NEMO gene have been reported in association with hypohidrotic ectodermal dysplasia with immunodeficiency (HED‐ID), OL‐HED‐ID, and incontinentia pigmenti. In this case, we report a novel mutation in the NEMO gene associated with OL‐HED‐ID. This article highlights the dermatologic manifestations of a rare disorder, OL‐HED‐ID, and underscores the importance of early recognition and prompt intervention to prevent life‐threatening infections.